The use of proteomic technologies in breast cancer research - Mazur, M.G.; Pyatchanina, T.V. (Experimental Oncology, 2016)
The main findings in the field of breast cancer proteomic research as well as modern strategies, technologies and methods of validation are reviewed. A special attention is focused on validated proteomic biomarkers of breast cancer. The data on proteomic profiling of stroma, tumor microenvironment, involvement of proteins in tumor progression, invasion and metastasis, and mechanisms of action of new generation drugs, are analyzed. The results of proteomic analysis are of high clinical importance and significantly improve tumor molecular profiling, stratification of patients, screening, diagnostics, and therapy of breast cancer.